Islam and Women's Role in Muslim Families in Domestic Waste Management for a Sustainable Environment in Coastal Areas (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This research aims to examine Islam and the role of Muslim family women in domestic waste management for environmental sustainability in coastal areas. This research method is a mixed method, collecting qualitative and quantitative data. Data collection techniques include observation, questionnaires, interviews and documentation. Problems are discussed using qualitative and quantitative approaches from methodological aspects. Environmental and religious approaches from scientific aspects. The data that has been collected is analyzed using descriptive analysis. The results of this research show that women from Muslim families as the smallest part of society have a very important role in increasing environmental awareness and managing domestic waste wisely in coastal areas. Through recitation communities, increasing knowledge and positive attitudes towards the environment for Muslim women in coastal areas will increase. Islam teaches its followers to maintain cleanliness and preserve nature as part of their worship. Muslim women who understand religious laws regarding the importance of keeping the environment clean, can teach and apply the values of caring for the environment in their families and pass them on to other families. So that collectively Muslim women can create clean seas and a sustainable environment. Good waste management is not only beneficial for the environment, but is also a real form of worship to Allah SWT.
Keywords: Islam; Muslim Family Women; Domestic Waste; Environment